Efektivitas ekstrak etanol bayam merah (amaranthus tricolor l.) Terhadap glukosa darah Tikus putih ( rattus novergicus) jantan Yang dipapar dengan asap rokok - suryanita suryanita; Ferna Indrayani; Muhammad Asri (State University of Gorontalo, 2022)
Research has been carried out on the effect of giving ethanol extract of red spinach (Amaranthus tricolor L.) on blood glucose of male white rats (Rattus novergicus) exposed to cigarette smoke for an interval of 15 days with the administration of ethanolic extract of red spinach. This study aims to determine the effect of ethanol extract on blood glucose levels of male white rats which were divided into 4 groups. Group I as a positive control that was not given any treatment, group II was given ethanolic extract of red spinach 200 mg/kg BW, group III was given ethanolic extract of red spinach 400 mg/kg BW, and group IV as a negative control was only given cigarette smoke exposure without any treatment. extract administration. From the research that has been done, the results of the decrease in blood glucose in group I is 63,3 mg/dl, group II is 98 mg/dl, group III is 116 mg/dl, and group IV is 155 mg/dl. Based on the results obtained, it can be concluded that the decrease in blood glucose caused The most effective is red spinach ethanol extract with a concentration of 200 mg/kg BW, which is 98 mg/dl.